KOMODIFIKASI BUDAYA ISLAM DALAM MASYARAKAT VIRTUAL - Hilda Syaf'aini Harefa (Central Library of Universitas Sebelas Maret, 2018)
Social media not only makes the user a communicator but can move public space. Social media becomes a forum where fellow users are related and have their own constructions. At this stage social media presents the wearer both individually and in groups. Currently in public spaces, hijab has become an increasingly common sight. Almost no place, circle or institution is not touched by the hijab. The spread of the use of hijab as a fashion trend among young people today is dominated by figures from Dian Pelangi and the Hijabers Community. Hijabers Community, has constructed the meaning of hijab according to their own. There is a shift in the meaning of the veil itself. Headscarves of the past and present have different meanings. In the past wearing a headscarf was a symbol of women’s obedience to the teachings of their religion, while now wearing a headscarf became a lifestyle pattern. Muslim fashion is undergoing a very rapid change and the presence of models that are good looking, stylish, and fashionable. This Hijabers phenomenon can not be separated from the use of social media, namely Instagram as a virtual public space. Through the instagram of Muslim women today the dialogue is their identity through their appearance. Appearances on Instagram contribute to interpreting the discourse about beautiful concepts by Muslim women. Through an existing Instagram account, it becomes a space to show someone in the virtual world. Instagram, which is a friend network, has indirectly formed a virtual community.